RESPOSTA DA AVEIA PRETA (Avena strigosa SCHREB) À IRRIGAÇÃO POR ASPERSÃO E ADUBAÇÃO NITROGENADA - Luz, Pedro Henrique de Cerqueira; Herling, Valdo Rodrigues; Braga, Gustavo José; Nogueira Filho, José Carlos Machado; Lima, César Gonçalves de (REVISTA DE AGRICULTURA, 2015)
RESPOSTA DA AVEIA PRETA (Avena strigosa SCHREB) À IRRIGAÇÃO POR ASPERSÃO E ADUBAÇÃO NITROGENADA